Answer: the numbers are 3 and -3
Explanation:
let the unknown number be x
The first UNKNOWN NUMBER = X
The second unknown number is = 6 + x
Their product = -9
(X)(6 + X) = -9
6x +
=-9
+6x +9=0
we multiply the coefficient of x which is 1 with 9
now, we look for two numbers that when multiplied will give us 9 and when added will give 6 and that is 3 and 3
+3x+3x +9 = 0
x(x+3) +3(x+3) = 0
(x +3 ) = 0
or (x +3)=0
x +3 =0
x=0 -3
x =-3
x +3=0
x =0-3
x =-3
since the numbers are the same ,we pick one
therefore,the first number =x =-3
the second number is 6 + x=6 + (-3)
6-3=3